Valley of the giant skeletons - Cernuschi, Claudio; Aliprandi, Christian (New York, N.Y. : Scholastic Inc., 2007)
When Geronimo gets lost looking for hidden treasures in the Gobi Desert, he comes across giant dinosaur bones.
English translation of La Valle degli Scheletri Giganti by Edizioni Piemme S.p.A.
G4
Keywords: Treasure troves -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Fiction; Mice -- Fiction; Dinosaurs -- Fiction; Fossils -- Fiction; Humorous stories; Stilton, Geronimo (Fictional character) -- Fiction; Mice -- Fiction; Dinosaurs -- Fiction; Fossils -- Fiction; Humorous fiction; Gobi Desert (Mongolia and China) -- Juvenile fiction; Gobi Desert (Mongolia and China) -- Fiction; Gobi Desert (Mongolia and China) -- Fiction